Study of Catalytic Properties of the HoxMg1-xAl2O4 Modified HZSM-5 Zeolite in Conversion of Methanol to C2-C4 Alkenes and p-Xylene - Natavan I. Makhmudova; Eyyub S. Mammadov; Fuad Sh. Kerimli; Teymur M. Ilyasli; Nargiz Firudin Akhmedova; Sabit E. Mammadov (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Selective conversion of methanol to C2-C4 alkenes and p-xylene is one of the appealing chemical routes. Currently, there are no effective catalysts for the co-production of C2-C4 alkenes and p-xylene from methanol. To date, modified medium-pore ZSM-5 zeolites are considered one of the excellent candidates for the development of selective catalysts for the conversion of methanol to lower alkenes and aromatic hydrocarbons. In this paper, nanosized (30-33nm) powders of HoхMg1-хAl2O4 spinel structure were obtained by the method of combustion of nitrate solutions of aluminium, magnesium, holmium, diethylmalonate and hydrazine monohydrate with the further calcination of nanopowders at 1000 °C. Obtained nanopowders used in the preparation of a solid-phase catalytic composition of HoхMg1-хAl2O4-HZSM-5. Various physico-chemical properties of the catalytic composition were investigated using X-ray diffraction (XRD), pyridine adsorption (BİO-RAD FTS 3000 MX) and low-temperature nitrogen adsorption (BET) techniques. The textural properties and acidity of the catalysts were altered by adjusting the nanopowder concentration (1.0-5.0 wt.%) in the catalytic composition. The conversion of methanol in the presence of the catalytic compositions was carried out in flow-type fixed-bed catalytic reactor at 400 °C, in the presence of nitrogen carrier gas with 1.0 h-1 flow rate. A correlation between the selectivity to C2-C4 alkenes and p-xylene with a ratio of Lewis (L) and Brønsted (B) acid sites and the volume of the catalyst pore, the amount of the modifier in the catalytic system has been established. As the amount of HoхMg1-хAl2O4 nanopowder increases, the ratio of B/L acid sites and the volume of the catalyst pore decrease, which play a significant role in the increase of the selectivity to C2-C4 alkenes and p-xylene. Maximum yield of C2-C4 alkenes (31.6%) and selectivity to p-xylene (80.5%) is achieved on a catalytic composition containing 5.0 wt.% HoxMg1-xAl2O4. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).